Epidemiological study of socio demographic factors in relation to depression among the elderly people in a rural area of Chittoor district of Andhra Pradesh, India - Udayar, Sharvanan Eshwaran; Prasad, Devi Vara (International Journal Of Community Medicine And Public Health, 2017)
Background: Population ageing is a major global demographic trend in the twenty-first century and is progressing at a rapid phase in developing countries. Depression is a common mental disorder in the old age and it continues to be an under-recognized and undertreated disorder particularly in rural areas. The main objective of the study was to assess the prevalence of depression among elderly persons living rural area and to determine the factors influencing it so that appropriate preventive measures can be recommended. Methods:Community based cross sectional study was undertaken in of Chittoor District in Andhra Pradesh state. Data was collected regarding socio-demographic profile and depression by using a semi structured and pretested questionnaire & analyzed using SPSS software. Results: Of the 451 subjects who participated in the study, the overall prevalence of depression among the studied population was 38.8%.Females with depression (47.5%) were more, compared to males (32%). Depression among 60-69 years age group people was more (44.5%) than remaining age groups. Depression was high among people who were alone like widowed, divorced, illiterate, poor socio economic status. Conclusions:There is high prevalence of depression and is significantly associated with various socio demographic factors considered in the study.